Demographics, technology acceptance, and willingness to pay: a pilot study on urban air mobility adoption in Indonesia - Fitri Trapsilawati; Trusti Hapsari; Iqbal Fikri; Muhammad Addinul Haniv; Widya Sari; Zainal Arifin Harahap (Sustainable Futures)
Urban Air Mobility (UAM) is an emerging trend in global transportation, with expectations for large-scale expansion in the near future. However, the widespread implementation of passenger drones requires further analysis, particularly regarding user characteristics, behavioural tendencies, and market dynamics. This study examines UAM adoption in archipelagic developing countries, with a specific focus on Indonesia. A total of 434 respondents participated in an online survey and experimental study. The findings indicate that residential area (p = 0.026) and prior experience with air transportation (p = 0.046) significantly influence the intention to adopt UAM. Additionally, four key constructs (i.e., perceived ease of use, attitude toward using technology, social influence, and self-efficacy) were found to be significant determinants of adoption intention. Notably, social influence had the strongest effect on adoption decisions in Indonesia. The study also explores the average adoption fare rate and its influencing factors. Results suggest that the estimated adoption fare for UAM in Indonesia is approximately IDR 14,000 (about US$1) per kilometre, twice the rate of traditional taxicab fares. These findings shed light on directions for future research especially in the importance of considering potential users’ characteristics, behaviours, and preferences when introducing UAM technology. Prior to implementation, future UAM studies should pay careful attention to adoption rates and pricing strategies to ensure market feasibility and user acceptance.